A (AlFeCoNi)C high entropy carbide ceramic coating and preparation method thereof

Magnetic sputtering method (ALFECONI) C high entropy carbonized ceramic coating to control the carbon atomic content and chemical bond structure, solve the problem of insufficient brittle and toughness of high -entropy carbonized ceramic coating, realize the characteristics of ceramics and metal characteristics Together, it significantly improves the toughness and protective performance of the coating.

CN118064858BActive Publication Date: 2025-01-24MIANYANG TEACHERS COLLEGE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410220272.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-28
Publication Date
2025-01-24
Estimated Expiration
2044-02-28

AI Technical Summary

Technical Problem

The existing high entropy carbide ceramic coatings have high brittleness and poor toughness, making it difficult to provide effective protection in impact loads, micro-movement wear and fatigue wear environments.

Method used

Use the magnetic sputtering method (ALFECONI) C high -entropy carbonized carbonized ceramic coating. By controlling the proportion of reaction gas flow to working gas flow, the carbon atomic content is less than 35%, forming a structure of covalent and metal bonds. Combined with the toughness of metal.

Benefits of technology

The coating has both the high hardness of the ceramics and the high toughness of the metal, showing the characteristics of strong toughness, which is significantly better than the toughness of the ceramic coating of the high -entropy carbonized carbonizer. Damage the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118064858B_ABST
    Figure CN118064858B_ABST
Patent Text Reader

Abstract

The invention discloses an (AlFeCoNi)C high entropy carbide ceramic coating and a preparation method thereof, wherein the coating is prepared by a magnetron sputtering method. Using metal Al, Fe, Co and Ni as target materials, using high-purity Ar as working gas, and C2H2 or CH4 as reaction gas, a target current is applied to the AlFeCoNi metal target, a bias voltage is applied to the substrate, and the ratio of the reaction gas flow rate to the working gas flow rate is controlled to be 1:40 to 1:5, and the (AlFeCoNi)C high entropy carbide ceramic coating is deposited on the surface of the substrate to be deposited; after the coating deposition is completed, it is cooled to below 50°C in a vacuum environment, and then air is filled into the cavity to atmospheric pressure, and the cavity is opened for sampling to obtain the (AlFeCoNi)C high entropy carbide ceramic coating on the surface of the substrate. During the deposition process, the content ratio of carbon atoms in the coating is regulated by controlling the reaction gas flow rate / working gas flow rate ratio, so that the carbon atom content is less than 35%. The prepared (AlFeCoNi)C high entropy carbide ceramic coating retains the high hardness of the traditional ceramic coating and has the high toughness of the metal, showing the characteristics of strong and tough integration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high entropy ceramic materials, in particular to an (AlFeCoNi)C high entropy carbide ceramic coating and a preparation method thereof. Background Art

[0002] High entropy materials are a new type of material developed in recent years. Their high entropy thermodynamic characteristics show many novel properties, providing important scientific inspiration and broad research space for cutting-edge fields. Ceramics formed by the reaction of four or more metal elements and non-metal elements in nearly equal proportions are called high entropy ceramics. High entropy carbide ceramics are favored by researchers for their unique composition, microstructure and good mechanical properties. High entropy carbide ceramic coatings have excellent properties such as high hardness, radiation resistance, oxidation resistance and wear resistance, and are a protective coating material with great application potential.

[0003] For example, patent CN202311206125.5 discloses a (MoNbTaTiW)C5 high entropy carbide ceramic prepared by SPS sintering, and the test results show that it has high hardness and low thermal conductivity. Patent CN202311019360.1 prepared a (HfNbZrTaW)C high entropy carbide ceramic with excellent wear resistance. Patent CN202211459351.X developed a (HfMoNbTaTi)C self-lubricating high entropy carbide ceramic. The structure of the above-mentioned high-entropy carbide ceramic is similar to that of traditional binary carbides such as TiC. It can be regarded as a face-centered cubic structure obtained by replacing the lattice sites of Ti with refractory elements such as Hf, Nb, Zr, Ta, and W. The metals are combined with C to form strong covalent bonds. This ceramic exhibits high hardness, but the strong covalent bonds in this material make it difficult for dislocations to slip and difficult to produce plastic deformation, which inevitably retains the brittleness of the ceramic coating and has the problem of lack of toughness. Summary of the invention

[0004] In view of the problem that the existing high entropy carbide ceramic coating is brittle and has poor toughness, the present invention provides an (AlFeCoNi)C high entropy carbide ceramic coating and a preparation method of the coating. The coating retains the high hardness of the traditional ceramic coating and has the high toughness of the metal, and has a good protective effect on the precision parts serving in the environment of impact load, fretting wear and fatigue wear.

[0005] The (AlFeCoNi)C high entropy carbide ceramic coating provided by the present invention is made by magnetron sputtering. Using metal Al, Fe, Co and Ni as target materials, high-purity Ar as working gas, C2H2 or CH4 as reaction gas, applying target current to the AlFeCoNi metal target, controlling the ratio of reaction gas flow rate to working gas flow rate to be 1:40 to 1:5, and depositing the (AlFeCoNi)C high entropy carbide ceramic coating on the surface of the substrate to be deposited.

[0006] The specific preparation method is as follows:

[0007] S1. Clean the surface of the substrate to be deposited before plating: The cleaning process includes ultrasonic cleaning in acetone and alcohol, respectively, and then plasma glow discharge cleaning. Plasma glow discharge cleaning refers to placing the substrate in a vacuum equipment cavity, introducing Ar gas after vacuum is established, applying a cleaning voltage on the substrate, establishing Ar plasma, and bombarding the substrate for sputtering cleaning. The substrate to be deposited is preferably stainless steel.

[0008] S2, using AlFeCoNi metal as the target, the chamber was evacuated to less than 2×10 -3 Pa, Ar gas is introduced into the vacuum chamber, and then C2H2 reaction gas is introduced into the chamber, the gas pressure in the chamber is maintained at 0.2-2.0 Pa, a pulse power supply is applied to the AlFeCoNi target, a bias voltage is applied to the substrate, and an (AlFeCoNi)C high entropy carbide ceramic coating is deposited on the surface of the substrate to be deposited; after the coating deposition is completed, it is cooled to below 50°C in a vacuum environment, and then air is filled into the chamber to atmospheric pressure, the chamber is opened for sampling, and an (AlFeCoNi)C high entropy carbide ceramic coating is obtained on the surface of the substrate.

[0009] Preferably, the power applied to the AlFeCoNi metal target is 600-2500W.

[0010] Preferably, the purity of the reaction gas and the working gas is both above 99.9%.

[0011] The percentage content of carbon atoms in the (AlFeCoNi)C high entropy carbide ceramic coating prepared by the above method is less than 35%.

[0012] Compared with the prior art, the present invention is beneficial in that:

[0013] (1) In the present invention, the ratio of the content of carbon atoms in the coating is regulated by controlling the ratio of the reaction gas flow rate / working gas flow rate (i.e., the ratio of C2H2 / Ar or the ratio of CH4 / Ar) during the deposition process, so that the carbon atom content is less than 35%, so that the number of carbon atoms dissolved in the metal lattice can be controlled. Since the radius of C atoms is small, the phase structure of the coating does not change after the C atoms enter, and remains a BCC structure. The chemical bonds in this type of high entropy carbide ceramic coating are mainly covalent bonds (metal-carbon) and metal bonds. This bonding form allows the material to have the characteristics of both ceramics and metals, with both the hardness of ceramics and the toughness of metals, showing the characteristics of strong and tough integration. By controlling the content of carbon atoms, the number of carbon atoms dissolved in the coating (i.e., the number of covalent bonds) and the grain size can be regulated to affect its mechanical properties. Studies have found that when the carbon atom content in the coating exceeds the solubility of the system (about 35%), the excess carbon atoms will precipitate to form amorphous carbon, and the coating will form a two-phase structure, i.e., amorphous carbon + BCC, becoming another coating different from the coating of the present invention.

[0014] (2) The present invention selects elements from the perspective of mixing enthalpy so that carbon atoms and metal atoms cannot form ionic bonds, thereby obtaining a structure in which carbon atoms are solid-dissolved in the metal lattice, and the chemical bonds are mainly covalent bonds and metallic bonds, thereby obtaining a (AlFeCoNi)C high-entropy carbide ceramic coating with excellent toughness. The mixing enthalpies of the metal components Al, Fe, Co, and Ni selected by the present invention with C atoms are -36, -50, -42, and -39 kJ / mol, respectively. The mixing enthalpies are close and the absolute values ​​are all smaller than those of strong carbide elements (such as Ti-C mixing enthalpy is -118 kJ / mol), which is conducive to inhibiting the formation of ionic bonds and facilitating the formation of metal-carbon covalent bonds. The coating of the present invention is significantly different from the existing high-entropy carbide coatings in which C atoms occupy the lattice lattice to form ionic bonds.

[0015] (3) The super-tough (AlFeCoNi)C high-entropy carbide ceramic coating prepared by the present invention has excellent properties of strong-toughness integration, wear resistance and friction reduction, and has a toughness advantage that is significantly superior to refractory high-entropy carbide ceramic coatings. It has great application prospects in impact loads and complex high-wear environments.

[0016] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The cross-sectional morphology of the coatings in Examples 1 and 2 and Comparative Examples 1 and 2 are tested using a scanning electron microscope.

[0018] Figure 2The diagram is a phase structure result diagram obtained by X-ray diffraction test of the coating in Examples 1 and 2 and Comparative Examples 1 and 2.

[0019] Figure 3 Graph showing the Vickers indentation test results of the coatings in Examples 1 and 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0020] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0021] Example 1

[0022] The (AlFeCoNi)C high entropy carbide ceramic coating was prepared on 304 stainless steel. The preparation method is as follows:

[0023] (1) Pre-plating treatment

[0024] The 304 stainless steel substrate was ultrasonically cleaned in acetone and alcohol for 10 minutes respectively. Then the 304 stainless steel substrate was placed in the magnetron sputtering equipment chamber and the vacuum was pumped to 1.00×10 -3 Pa; then 60 sccm of 99.999% pure Ar gas is introduced into the chamber, the gas pressure is adjusted to 3.5 Pa by controlling the pumping speed, a cleaning voltage of -1300 V is applied to the substrate, and the substrate is continuously sputtered and cleaned for 30 minutes.

[0025] (2) Deposition of (AlFeCoNi)C high entropy carbide ceramic coating

[0026] With AlFeCoNi metal with a purity of 99.9% as the target, Ar gas with a flow rate of 40sccm is introduced into the vacuum chamber; then 1sccm of C2H2 reaction gas with a purity of 99.99% is introduced into the chamber, C2H2 / Ar=1:40, and the vacuum degree is maintained at 0.5Pa; a high-power pulse power supply with a power of 900W is applied to the AlFeCoNi target, and a -60V bias is applied to the substrate to deposit (AlFeCoNi)C high entropy carbide ceramic coating on the surface of the 304 stainless steel substrate for 40min. After the coating deposition is completed, it is cooled to below 50℃ in a vacuum environment, and then air is filled into the chamber to atmospheric pressure, and the chamber is opened for sampling to obtain (AlFeCoNi)C high entropy carbide ceramic coating on the substrate surface.

[0027] Example 2

[0028] In this embodiment, the substrate is exactly the same as the substrate in Example 1, and a (AlFeCoNi)C high entropy carbide ceramic coating is prepared on the surface of the substrate. The preparation method is as follows:

[0029] (1) The same as step (1) in Example 1;

[0030] (2) Deposition of (AlFeCoNi)C high entropy carbide ceramic coating

[0031] With AlFeCoNi metal with a purity of 99.9% as the target, Ar gas with a flow rate of 40sccm is introduced into the vacuum chamber; then 5sccm C2H2 reaction gas with a purity of 99.99% is introduced into the chamber, C2H2 / Ar=1:8, and the vacuum degree is maintained at 0.6Pa; a high-power pulse power supply with a power of 900W is applied to the AlFeCoNi target, and a -60V bias is applied to the substrate to deposit (AlFeCoNi)C high entropy carbide ceramic coating on the surface of the 304 stainless steel substrate for 40min. After the coating deposition is completed, it is cooled to below 50℃ in a vacuum environment, and then air is filled into the chamber to atmospheric pressure, and the chamber is opened for sampling to obtain (AlFeCoNi)C high entropy carbide ceramic coating on the substrate surface.

[0032] Comparative Example 1

[0033] The (TiNbZrCr)C high entropy carbide ceramic coating is prepared on 304 stainless steel. The preparation method is as follows:

[0034] (1) The same as step (1) in Example 1;

[0035] (2) Deposition of (TiNbZrCr)C high entropy carbide ceramic coating

[0036] With 99.9% pure TiNbZrCr metal as the target, 40sccm Ar gas is introduced into the cavity, and then 4sccm C2H2 with a purity of 99.99% is introduced into the cavity as the reaction gas, C2H2 / Ar=1:10, and the vacuum is maintained at 0.6Pa; a high-power pulse power supply with a power of 900W is applied to the TiNbCrZr target, a -60V bias is applied to the substrate, and a (TiNbZrCr)C high-entropy carbide ceramic coating is deposited on the substrate surface for 30min. After the coating deposition is completed, it is cooled to below 50°C in a vacuum environment, and then air is filled into the cavity to atmospheric pressure, and the cavity is opened for sampling to obtain a (TiNbZrCr)C high-entropy carbide ceramic coating on the substrate surface.

[0037] Comparative Example 2

[0038] In this embodiment, the substrate is exactly the same as the substrate in Example 1, and a (AlFeCoNi)C / aC high entropy carbide / amorphous carbon ceramic coating is prepared on the surface of the substrate. The preparation method is as follows:

[0039] (1) The same as step (1) in Example 1;

[0040] (2) Deposition of (AlFeCoNi)C / aC high entropy carbide / amorphous carbon ceramic coating

[0041] With AlFeCoNi metal with a purity of 99.9% as the target, Ar gas with a flow rate of 40sccm is introduced into the vacuum chamber; then 10sccm of C2H2 reaction gas with a purity of 99.99% is introduced into the chamber, C2H2 / Ar=1:4, and the vacuum degree is maintained at 0.6Pa; a high-power pulse power supply with a power of 900W is applied to the AlFeCoNi target, and a -60V bias is applied to the substrate to deposit (AlFeCoNi)C / aC high entropy carbide / amorphous carbon ceramic coating on the surface of the 304 stainless steel substrate for 30min. After the coating deposition is completed, it is cooled to below 50℃ in a vacuum environment, and then air is filled into the chamber to atmospheric pressure, and the chamber is opened for sampling to obtain (AlFeCoNi)C / aC high entropy carbide ceramic coating on the substrate surface.

[0042] The high entropy carbide ceramic coatings prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were tested as follows:

[0043] (1) The cross-sectional microstructure of the high entropy carbide ceramic coating was tested using a field emission scanning electron microscope (SEM). The test results are shown in Figure 2. Figure 1 As shown. It can be seen that the cross-sectional microstructure of the coating of Example 1 is a dense columnar crystal structure. The cross-sectional microstructure of the coating of Example 2 is a dense and smooth morphology structure. The coating of Comparative Example 1 is a columnar crystal structure, and the fracture surface is uneven, showing the characteristics of brittle fracture. The coating of Comparative Example 2 is also a brittle fracture morphology structure.

[0044] (2) X-ray diffractometer (XRD) was used to test the phase structure of high entropy carbide ceramic coating. The test results are as follows: Figure 2 As shown. It can be seen that the coatings of Example 1 and Example 2 are both single-phase BCC structures. The coating of Comparative Example 1 is a single-phase FCC structure. The coating of Comparative Example 2 contains BCC structure and amorphous structure. This is because the carbon atom content of the coating in Comparative Example 2 is 55%, which is higher than 35%. The excess carbon atoms will precipitate to form amorphous carbon, and then form a dual-phase structure of amorphous carbon + BCC.

[0045] (3) The high entropy carbide ceramic coating was indented using a Vickers hardness tester with a maximum load of 25 g to determine the toughness of the coating. Figure 3As shown. It can be seen that the coating sample of Example 1 has no obvious cracks in the indentation, indicating that the coating has excellent toughness. The coating sample of Example 2 has tiny cracks in the indentation, but no peeling, indicating that the coating still has excellent toughness. The cracks around the indentation of the coating of Comparative Example 1 expand and cause the coating to peel off, indicating that the coating toughness is poor. The coating sample of Comparative Example 2 has obvious cracks around the indentation, indicating that the coating toughness is relatively poor.

[0046] (4) The hardness of the coating was measured using a nano indenter (Nano Indenter G200). Table 1 shows the deposition conditions, elemental composition and hardness of the coating in Examples 1 and 2 and Comparative Examples 1 and 2. It can be seen that the hardness of Example 1 and Example 2 reaches 13 GPa and 16.2 GPa respectively.

[0047] Table 1. Deposition conditions, elemental composition and hardness results of the coatings in Examples 1, 2 and Comparative Examples 1, 2

[0048]

[0049] The above test results show that the (AlFeCoNi)C high entropy carbide ceramic coating of the present invention has the characteristics of both ceramics and metals, with both the hardness of ceramics and the toughness of metals, reflecting the characteristics of strong and tough integration. Although the coatings of comparative documents 1 and 2 have good hardness, their toughness is poor and they do not have the characteristics of strong and tough integration.

[0050] In summary, in the novel (AlFeCoNi)C high entropy carbide ceramic coating provided by the present invention, C atoms with smaller atomic radius are dissolved in the lattice formed by metal atoms, the proportion of C atoms is low, and there are covalent bonds and metal bonds in the coating. It has both the hardness of ceramics and the toughness of metals, and has strong and tough integration characteristics, which greatly improves the plastic deformation ability of the coating. This (AlFeCoNi)C high entropy carbide ceramic coating has a significantly better toughness advantage than refractory high entropy carbide ceramic coatings.

[0051] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an (AlFeCoNi)C high entropy carbide ceramic coating, characterized in that: The magnetron sputtering method is adopted, with metal Al, Fe, Co and Ni as target materials, high-purity Ar as working gas, C2H2 or CH4 as reaction gas, and target current is applied to the AlFeCoNi metal target. The content of carbon atoms in the coating is regulated by controlling the ratio of reaction gas flow rate to working gas flow rate to be 1:40~1:5, so that the percentage of carbon atoms is 5-35%, and (AlFeCoNi)C high entropy carbide ceramic coating is deposited on the surface of the substrate to be deposited; the preparation steps are as follows: S1. Cleaning the surface of the substrate to be deposited; S2, using AlFeCoNi metal as the target, the chamber was evacuated to less than 2×10 -3 Pa, Ar gas is introduced into the vacuum chamber, and then C2H2 reaction gas is introduced into the chamber, a pulse power supply is applied to the AlFeCoNi target, a bias voltage is applied to the substrate, and an (AlFeCoNi)C high entropy carbide ceramic coating is deposited on the surface of the substrate to be deposited; the air pressure in the chamber is maintained at 0.2-2.0 Pa during the deposition process; after the coating deposition is completed, it is cooled to below 50°C in a vacuum environment, and then air is filled into the chamber to atmospheric pressure, the chamber is opened for sampling, and an (AlFeCoNi)C high entropy carbide ceramic coating is obtained on the surface of the substrate, and the ceramic coating has a single-phase BCC structure.

2. The method for preparing the (AlFeCoNi)C high entropy carbide ceramic coating according to claim 1, characterized in that: The power applied to the AlFeCoNi metal target is 600-2500W.

3. The method for preparing the (AlFeCoNi)C high entropy carbide ceramic coating according to claim 1, characterized in that: The purity of the reaction gas and the working gas is both above 99.9%.

4. The method for preparing the (AlFeCoNi)C high entropy carbide ceramic coating according to claim 1, characterized in that: In step S1, the substrate to be deposited is made of stainless steel.

5. The method for preparing the (AlFeCoNi)C high entropy carbide ceramic coating according to claim 1, characterized in that: In step S1, the cleaning process includes ultrasonic cleaning in acetone and alcohol respectively, and then plasma glow discharge cleaning.

6. A (AlFeCoNi)C high entropy carbide ceramic coating, characterized in that: The coating is prepared by the (AlFeCoNi)C high entropy carbide ceramic coating preparation method described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • A high-performance single-phase self-lubricating high-entropy ceramic material and its preparation method

    CN115925423B

  • High-entropy carbide ceramic for spent fuel shielding material and preparation method of high-entropy carbide ceramic

    CN117049880A

  • High-entropy carbide ceramic (MoNbTaTiW) C5 and preparation method thereof

    CN117105664A

  • Light-weight high-entropy alloy and manufacturing process of impeller made of light-weight high-entropy alloys

    CN110396634A